Interpersonal Emotion Regulation: From Research to Group Therapy - Messina, Irene; Calvo, Vincenzo; Masaro, Chiara; Ghedin, Simona; Marogna, Cristina (Frontiers in Psychology, 2021)
Even if the most part of emotion regulation studies have considered the individual in isolation, individuals often regulate their emotions in interpersonal interactions. In the present article, we review interpersonal emotion regulation (IER) definitions, classifications of IER strategies and clinical conceptualization of IER as an important dimension for mental health. All these elements have relevant implications for group therapy, including non-specific group therapeutic factors and group therapeutic techniques aimed to the promotion of adaptive regulation as part of the group experience and of awareness of IER behaviours by observing their spontaneous emersion in group therapy settings .